PENERAPAN MODEL PBL DENGAN PENDEKATAN CRT UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V - Vivi Dwi Ramadhani; Savitri Suryandari; Mahyuni Rahayu (EDUCATIONAL JOURNAL : General and Specific Research, 2025)
This study aims to improve the learning outcomes of grade V students in IPAS subjects through the application of the Problem-based learning (PBL) learning model with a Culturally Responsive Teaching (CRT) approach at SDN Pakis 1 Surabaya. This is a Classroom Action Research (PTK) with reference to the Kurt Lewin model. The subjects of this study were students of class V-A SDN Pakis 1 Surabaya in the academic year 2024/2025 as many as 28 students. This research is based on several considerations that show that the low learning outcomes of students are characterized by several students obtaining IPAS scores below KKTP 75. Some of the factors that influence low learning outcomes include a lack of understanding of concepts, low student motivation, minimal student participation in the learning process, and the incompatibility of the material with the reality of their daily lives. The way researchers collect data uses the test method. Indicators of success in the study can be measured from the acquisition of student learning outcomes that show in cycle 1 student learning outcomes reached 82% completeness and in cycle 2 reached 93% completeness which before class action research was carried out student learning outcomes reached 71% completeness. Through the application of the Problem-based learning model with the Culturally Responsive Teaching (CRT) approach. has a significant impact on improving student learning outcomes in IPAS subjects. Indicating that the learning approach.